2018
DOI: 10.1108/heswbl-05-2017-0030
|View full text |Cite
|
Sign up to set email alerts
|

The impact of workplace placement on students’ entrepreneurial attitude

Abstract: 2Purpose: The aim of the research was to determine the impact of a workplace placement on 3 the student participants' self-reported entrepreneurial attitude (EA) 4Design/methodology/Approach: A review of relevant literature informed questions 5 incorporated in the university's annual feedback questionnaire completed by students (n = 6 461) on return from a work placement of between 44 and 52 weeks. 7 Findings:The study has shown that both gender and entrepreneurial legacy influence 8 baseline and post-placemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 18 publications
1
8
0
1
Order By: Relevance
“…Historically, agriculture has been considered as an inflexible, low-tech industry dominated by family businesses that are mostly focused on doing things better rather than doing new things, although market influences mean that entrepreneurial behaviour is often seen as an asset within the sector (Lans et al, 2013). Indeed, entrepreneurship is vital for economic transformation, stimulation of global development and is a wealth generator at individual, regional, national and international levels (Obembe et al, 2014;Manning and Parrott, 2018). In the case of land-based universities, consideration of what rural entrepreneurship encompasses is of interest.…”
mentioning
confidence: 99%
“…Historically, agriculture has been considered as an inflexible, low-tech industry dominated by family businesses that are mostly focused on doing things better rather than doing new things, although market influences mean that entrepreneurial behaviour is often seen as an asset within the sector (Lans et al, 2013). Indeed, entrepreneurship is vital for economic transformation, stimulation of global development and is a wealth generator at individual, regional, national and international levels (Obembe et al, 2014;Manning and Parrott, 2018). In the case of land-based universities, consideration of what rural entrepreneurship encompasses is of interest.…”
mentioning
confidence: 99%
“…There are a number of contemporary literatures of interest that are considered: agricultural entrepreneurship, agri technology, the entrepreneurial farmer, rural entrepreneurship more widely, and then the specific aspects of entrepreneurial legacy and entrepreneurial bridging. Whilst entrepreneurial legacy is considered in current literature in terms of development and nurturing generational entrepreneurial behavior with families [62][63][64][65][66][67][68][69][70], what has been identified in this paper is how a university with an agri-technology incubator can in itself develop an ecosystem of entrepreneurial legacy. This is especially so when there is an interaction between existing students and businesses that are at all different stages on the ideation to fully commercialized journey.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst HAU does not have a specific entrepreneurship module, the one-year compulsory work placement has been shown to increase entrepreneurial attitude of the students that participated. Manning and Parrott's [69] study showed that weighted mean entrepreneurial attitude increased after placement for all students (n = 108) even when 77% of the students already came from a selfemployed or entrepreneurial background and the agricultural students mean weighted entrepreneurial attitude was higher than all other students on different programs.…”
Section: Course Offeringmentioning
confidence: 94%
See 1 more Smart Citation
“…No contexto estudantil, a atitude empreendedora tem se mostrado importante por possibilitar a avaliação da eficácia de práticas voltadas a fomentar a opção ocupacional pelo empreendedorismo (Ismail, 2015). Estudantes com maior nível de atitude empreendedora tendem a intencionar empreender com maior magnitude quando comparados àqueles com baixo nível do construto (Johnson & Mathew, 2017;Manning & Parrott, 2017). Numa perspectiva expandida, países em que os sujeitos exibem maiores níveis de atitude empreendedora tendem a apresentar maior nível de atividade empreendedora, o que demonstra a centralidade desse construto para predição do empreendedorismo como alternativa ocupacional (Draghici, Albulescu, & Tamasila, 2014).…”
Section: Introductionunclassified